2014
DOI: 10.1536/ihj.13-198
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Heart Rate Variability in Coronary Artery Disease Patients Affected by Thyroid Dysfunction

Abstract: SummarySubclinical hypothyroidism and hyperthyroidism have been recognized as clinical entities with negative effects on the cardiovascular system. Moreover, the effect of treated thyroid dysfunction on parameters associated with the cardiovascular control system has been poorly investigated. In the present study we analyzed time-domain heart rate variability in coronary artery disease (CAD) patients with known thyroid diseases. Twenty-four hour ECG monitoring was performed in 344 patients with coronary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Accordingly, previous studies with smaller sample sizes showed reduced variability in subjects with SCHyper compared to euthyroid ones (10,11,14,26). Goichot et al (11) detected lower values for SDNN in SCHyper subjects (N=12) compared to controls (N=32).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Accordingly, previous studies with smaller sample sizes showed reduced variability in subjects with SCHyper compared to euthyroid ones (10,11,14,26). Goichot et al (11) detected lower values for SDNN in SCHyper subjects (N=12) compared to controls (N=32).…”
Section: Discussionmentioning
confidence: 86%
“…Goichot et al (11) detected lower values for SDNN in SCHyper subjects (N=12) compared to controls (N=32). Galetta et al (28) (SCHyper: N=30; controls: N= 30), Petretta et al (10) (SCHyper: N=30; controls: N= 20), and Falcone et al (14) (SCHyper: N=28; controls: N=170; all with coronary artery disease), besides lower SDNN, also detected reduced RMSSD and pNN50 values when comparing both groups. It is noteworthy that we did not find a marked cardiac parasympathetic withdrawal in SCHyper subjects; however, this group showed lower values in magnitude for parasympathetic indices in comparison to euthyroids.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…HF is a marker of vagal efferent signal that is modulated by ventilation. [ 34 ] HRV parameters were lower in cases as compared to controls in both time and frequency domains. HRV measures fluctuations in the autonomic inputs to the heart.…”
Section: Discussionmentioning
confidence: 95%
“…Although there are evidence suggesting that strong reduction of BP does not reduce the rate of a composite outcome of fatal and nonfatal major cardiovascular events in type 2 diabetes patients, it is important to consider that most of these evidence were drawn from studies presenting some confounding factors such as the presence of previous CVD and events and the increase in cardiovascular outcomes found with excessive lowering of BP appeared at a level of BP <110 mmHg, a quite outlier values used for the development of recommendations and very rarely seen in patients with hypertension taking conventional treatment (9). On the other hand, despite the fact that some randomized controlled trials suggest that excessive reduction of BP is associated with an increase in cardiovascular mortality (10,11), there is still little evidence that this mortality excess is due to BP lowering. The recent findings of the study by Adamsson Eryd et al support this idea and relaunch the discussion on the J-shaped phenomenon of BP in type 2 diabetes patients (12).…”
Section: Introductionmentioning
confidence: 99%